Ovarian function and pregnancy rates in dairy goats that received 300 IU of human chorionic gonadotropin (hCG) intravaginally at the time of artificial insemination - Rodrigues, Juliana Nascimento Duarte (2023)
Two experiments were carried out to evaluate the effects of administering 300 IU hCG intravaginally (i.vag.) at the time of artificial insemination (AI) on ovulatory response, luteal function and pregnancy rates in cyclic Alpine (A) and Saanen (S) goats. All animals received two i.m. injections of 37.5 μg of D-cloprostenol (Prolise®; Tecnopec, São Paulo, SP, Brazil) at 11.5-day (Experiments 1 and 2) or 7.5-day intervals (Experiment 2). One day after the onset of estrus (day of AI=D0), the goats were randomly allocated to one of the two groups that received: 300 IU hCG (Vetecor®; Hertape-Calier, São Paulo, SP, Brazil) i.vag. (G-hCG; Experiment 1: n = 12 A; Experiment 2: n = 80 A + 63 S) or 0.3 mL or saline solution i.vag. (G-Control; Experiment 1: n = 12 A; Experiment 2: n = 82 A + 65 S). Blood samples for measurements of circulating progesterone concentrations were drawn on both days of D-cloprostenol injections and on D3, D7, D10, D13 and D21 (Experiment 1). Transrectal ovarian ultrasonography was done on D7, D10, D13, D17 and D21 (Experiment 1), and pregnancy detection was performed on D60 (Experiment 2). In Experiment 1, there were no differences (P > 0.05) in the mean diameter of ovulatory follicles, timing and number of ovulations, and incidence of early luteal regression between the two groups of goats. However, the total luteal area on D17 and D21 and luteal vascularization on D10 and D13 were higher (P < 0.05) in G-hCG compared with G-Control does. In Experiment 2, the pregnancy rate was higher (P < 0.05) in G-hCG compared with G-Control goats (80.4% compared with 67.3%, respectively). Human chorionic gonadotropin (300 IU) given i.vag. at the time of AI did not alter ovulatory response or progesterone secretory ability of resultant corpora lutea nor did it completely prevent premature luteal regression, but it increased the luteal area and luteal vascularization as well as the conception rate in dairy goats (the latter by 13.1%).